PENGARUH PENGAWASAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PADA KANTOR DINAS KEPENDUDUKAN DAN CATATAN SIPIL KOTA PEKANBARU - Raedi Fristiadi; Susi Hendriani; Yusni Maulida (Jurnal Ekonomi, 2018)
This study aims to determine the effect of supervision and organizational commitment to employees performance at the Office of Dinas Kependudukan dan Catatan Sipil Kota Pekanbaru. Respondents numbered 116 people. The method of analysis using multiple linear regression. The analysis results show that t arithmetic (2,927)> t table (1,981) or Sig. (0.004) <0.05. This means that supervision has a significant effect on performance. The analysis results show that t arithmetic (5,813)> t table (1,981) or Sig. (0,000) <0.05. This means that organizational commitment has a significant effect on performance. The analysis results show F arithmetic (55,685)> F table (3,076) with Sig. (0,000) <0.05. This means that the independent variables of monitoring and organizational commitment together have a significant effect on the dependent variable (performance). R Square value of 0.496. This means that the percentage of independent variable influence (supervision and organizational commitment) on the dependent variable (performance) is 49.6%. While the remaining 50.4% is influenced by other variables that are not included in this regression model.